Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If a,b,c,d are proportional, prove that a+d=b+c+ (a-b)(a-c) a

If a,b,c,d are proportional, prove that a+d=b+c+(a-b)(a-c)                                                                                     a

Grade:10

1 Answers

SHAIK AASIF AHAMED
askIITians Faculty 74 Points
7 years ago
Hello student,
Please find the answer to your question below
If a,b,c,d are proportional, To prove
a+d=b+c+((a-b)(a-c)/a)
a(a-b-c+d) = a^2-ab+ad=a^2 - ab - ac +bc = (a-b)(a-c);
a-b-c+d = +(a-b)(a-c)/a
Soa+d=b+c+((a-b)(a-c)/a)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free